ALVR109, an off‐the‐shelf partially HLA matched SARS‐CoV‐2–specific T cell therapy, to treat refractory severe COVID‐19 pneumonia in a heart transplant patient: Case report. Issue 4 (27th December 2021) - Martits‐Chalangari, Katalin; Spak, Cedric W.; Askar, Medhat; Killian, Aaron; Fisher, Tammy L.; Atillasoy, Ercem; Marshall, William L.; McNeel, David; Miller, Michael D.; Mathai, Susan K.; Gottlieb, Robert L.
Abstract : An unvaccinated adult male heart transplant recipient patient with recalcitrant COVID‐19 due to SARS‐CoV‐2 delta variant with rising nasopharyngeal quantitative viral load was successfully treated with ALVR109, an off‐the‐shelf SARS‐CoV‐2–specific T cell therapy. Background immunosuppression included 0.1 mg/kg prednisone, tacrolimus, and mycophenolate mofetil 1 gm twice daily for historical antibody‐mediated rejection. Prior therapies included remdesivir, corticosteroids, and tocilizumab, with requirement for high‐flow nasal oxygen. Lack of clinical improvement and acutely rising nasopharyngeal viral RNA more than 3 weeks into illness prompted the request of ALVR109 through an emergency IND. The day following the first ALVR109 infusion, the patient's nasopharyngeal SARS‐CoV‐2 RNA declined from 7.43 to 5.02 log10 RNA copies/ml. On post‐infusion day 4, the patient transitioned to low‐flow oxygen. Two subsequent infusions of ALVR109 were administered 10 and 26 days after the first; nasopharyngeal SARS‐CoV‐2 RNA became undetectable on Day 11, and he was discharged the following day on low‐flow oxygen 5 weeks after the initial diagnosis of COVID‐19. The clinical and virologic improvements observed in this patient following administration of ALVR109 suggest a potential benefit that warrants further exploration in clinical trials. Abstract : An unvaccinated adult male heart transplant recipient with recalcitrant COVID‐19 shows clinical and virologic improvement—including clearing the delta variant of SARS‐CoV‐2—after receiving ALVR109, an off‐the‐shelf T cell therapy specific for SARS‐CoV‐2.